Status and direction of youth development in the Philippines - Elevazo, Aurelio D. (Education quarterly.)
Youth development is a concern which could continue to either draw the best of all who are involved in it or cause a lot of empty eloquence. There is much to do. What Philippine society needs is more action, less verbalism, and even less of more palabas (empty ostentation). Youth development requires unconditional dedication and commitment to the betterment of the boys and girls who are top become men and women of the years ahead when many of us will have outlived our usefulness.